On the impact of covariate measurement error on spatial regression modelling. Issue 8 (9th October 2014) - Huque, Md Hamidul; Bondell, Howard D.; Ryan, Louise; Guttorp, Peter; Piegorsch, Walter W.
<x xml:space="preserve">Abstract</x> Spatial regression models have grown in popularity in response to rapid advances in geographic information system technology that allows epidemiologists to incorporate geographically indexed data into their studies. However, it turns out that there are some subtle pitfalls in the use of these models. We show that the presence of covariate measurement error can lead to significant sensitivity of parameter estimation to the choice of spatial correlation structure. We quantify the effect of measurement error on parameter estimates and then suggest two different ways to produce consistent estimates. We evaluate the methods through a simulation study. These methods are then applied to data on ischaemic heart disease. Copyright © 2014 John Wiley & Sons, Ltd.